Dyckia pseudodelicata, a new species of the D. selloa complex (Bromeliaceae, Pitcairnioideae) from Rio Grande do Sul, Brazil - Büneker, Henrique Mallmann; Mariath, Jorge Ernesto De Araujo (Phytotaxa, 2022)
We propose the new species Dyckia pseudodelicata which is described and illustrated here, and provide data on its distribution and habitat. We compare the new species to the related Dyckia delicata and highlight their morphological differences. Morphological features that have been little explored in Dyckia taxonomy proved to be diagnostic in our analysis, such as the presence and morphology of trichomes on the petal margins and the position of ovules in relation to the longitudinal axis of the ovary and their disposition in the placenta.